Machine Vision-Based Oil and Gas Pipeline Inspection Robot - Peng, Haoran; Wang, Hang; Bu, Penghui (International Journal of Computer Science and Information Technology, 2026)
Pipeline transportation is currently the main method for large-scale, long-distance transport of oil and natural gas. As the service life increases, the risk of pipeline leaks also gradually rises. Oil and gas pipeline inspection, as a key link in pipeline integrity, can provide a scientific basis for the prevention and maintenance of pipeline accidents. Pipeline robots play an important role in pipeline inspection, as they can enter complex pipeline environments to carry out tasks such as inspection, cleaning, and maintenance. At the same time, with the development of artificial intelligence, machine vision technology is widely applied in pipeline inspection. This paper provides a comprehensive review of pipeline inspection robots based on machine vision, including mechanical structures and visual inspection methods, and analyzes and compares their performance characteristics. It summarizes the factors limiting their development and proposes solutions, providing a reference for the further development of machine vision-based oil and gas pipeline inspection robots.